Quantification of human norovirus GII, human adenovirus, and fecal indicator organisms in wastewater used for irrigation in Accra, Ghana - Silverman, A.I.; Akrong, M.O.; Amoah, Philip; Drechsel, Pay; Nelson, K.L. (2013)
Quantitative microbial risk assessment (QMRA) is frequently used to estimate health risks associated with wastewater irrigation and requires pathogen concentration estimates as inputs. However, human pathogens, such as viruses, are rarely quantified in water samples, and simple relationships between fecal indicator bacteria and pathogen concentrations are used instead. To provide data that can be used to refine QMRA models of wastewater-fed agriculture in Accra, stream, drain, and waste stabilization pond waters used for irrigation were sampled and analyzed for concentrations of fecal indicator microorganisms (human-specific Bacteroidales, E. coli, Enterococci, thermotolerant coliform, and somatic and F+ coliphages) and two human viruses (adenovirus and norovirus genogroup II). E. coli concentrations in all samples exceeded limits suggested by the World Health Organization, and human-specific Bacteroidales was found in all but one sample, suggesting human fecal contamination. Human viruses were detected in 16 out of 20 samples, were quantified in 12, and contained 2–3 orders of magnitude more norovirus than predicted by norovirus to E. coli concentration ratios assumed in recent publications employing indicator-based QMRA. As wastewater irrigation can be beneficial for farmers and municipalities, these results should not discourage water reuse in agriculture, but provide motivation and targets for wastewater treatment before use on farms.